Assessing STEAM’s Impact on Marine Awareness: The Moderating Effect of Critical Thinking - Suharti Suharti; Hapidin Hapidin; Yufiarti Yufiarti (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
Marine environmental awareness in early childhood is essential to fostering lifelong environmental responsibility. This study evaluates the comparative effectiveness of STEAM and scientific approaches on children’s marine awareness, specifically examining the moderating role of critical thinking among second-grade students in West Java, Indonesia. Using a quasi-experimental design with a 2×2 factorial structure, the study involved 51 children aged 7–8 years. Data were collected using the New Environmental Paradigm (NEP) Scale adapted for children and a critical thinking assessment rubric, then analyzed using Two-Way ANOVA. Results confirmed that the STEAM approach significantly outperformed the scientific approach in enhancing marine awareness (F(1, 45)=111.65, p<.001). Crucially, a significant interaction effect (F(2, 45)=3.49, p=.039) revealed that the efficacy of STEAM was amplified in students with higher critical thinking skills (M=136.27) compared to the scientific group (M=112.75). Practically, these findings advocate for shifting early environmental pedagogy from linear scientific inquiry to transdisciplinary STEAM models. Educators are recommended to integrate critical thinking scaffolding within STEAM activities to maximize marine literacy and environmental responsibility in young learners.